2013
DOI: 10.1007/s11589-013-0021-4
|View full text |Cite
|
Sign up to set email alerts
|

Focal depth, magnitude, and frequency distribution of earthquakes along oceanic trenches

Abstract: The occurrence of earthquakes in oceanic trenches can pose a tsunami threat to lives and properties in active seismic zones. Therefore, the knowledge of focal depth, magnitude, and time distribution of earthquakes along the trenches is needed to investigate the future occurrence of earthquakes in the zones. The oceanic trenches studied, were located from the seismicity map on: latitude ?51°to ?53°a nd longitude-160°to 176°(Aleutian Trench), latitude ?40°to ?53°and longitude ?148°to ?165°(Japan Trench), and lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The b-value is the stress meter that indicates the level of tectonic stress accumulation in the earthquake-prone zones, Hammed et al (2019). The lower the b-value, the higher the tectonic stress and vice-versa (Awoyemi et al 2017;Hammed et al 2013). In this work, the b values obtained in all https://doi.org/10.5194/nhess-2020-128 Preprint.…”
Section: Trend Of Seismicity and Tectonic Characterization Along The mentioning
confidence: 67%
“…The b-value is the stress meter that indicates the level of tectonic stress accumulation in the earthquake-prone zones, Hammed et al (2019). The lower the b-value, the higher the tectonic stress and vice-versa (Awoyemi et al 2017;Hammed et al 2013). In this work, the b values obtained in all https://doi.org/10.5194/nhess-2020-128 Preprint.…”
Section: Trend Of Seismicity and Tectonic Characterization Along The mentioning
confidence: 67%
“…The focus of an earthquake is the actual point where the rocks break in the subsurface. The depths of the focus are categorized as shallow (0–70 km), intermediate (71–300 km), and deep depth (301–700 km below the earth surface) respectively [8] . Most earthquakes occurred at shallow depth, with total events of 76223, while deep depth had a total record of 61 times, with the magnitude ranging from 2 to 4.9.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The descriptive analysis has also been found useful in the evaluation of earthquake occurrence in a region. This ranged from description of earthquake occurrence by plotting the graphs of frequencies of earthquakes against their coordinates [5] , number of earthquakes against its magnitudes [7] , [8] , cumulative number of earthquake against its magnitude [7] , and measure of central tendencies [9] . It has been reported that study of previous and present activities of earthquake pattern is vital in prevention of lives and properties from earthquake destructions [9] .…”
Section: Datamentioning
confidence: 99%
“…This earthquake caused heavy damage and many casualties within villages more than 10 kilometers from the epicenter (Boyd et al, 2007b). and deep-focus earthquakes are 300 to 700 km (Hammed et al, 2013). Intermediate-depth earthquakes represent deformation within the subducted lithosphere beneath the Eurasian Plate, rather than shallow plate interfaces between subducting and overriding tectonic plates.…”
Section: Manuscript Submitted To Earth's Futurementioning
confidence: 99%